Pyruvate Kinase M2 Contributes to TLR-Mediated Inflammation and Autoimmunity by Promoting Pyk2 Activation - Zhang, Xin; Yang, Yonghong; Jing, Lina; Zhai, Weiwei; Zhang, Hui; Ma, Qun; Li, Chunxia; Yan, Fenglian; Cheng, Dalei; Zhang, Junfeng; Ning, Zhaochen; Shi, Hui; et al. (Frontiers in Immunology, 2021)
Toll-like receptors (TLRs) play critical roles in regulating the abnormal activation of the immune cells resulting in the pathogenesis of inflammation and autoimmune diseases. Pyruvate kinase M2 (PKM2), which governs the last step of glycolysis, is involved in multiple cellular processes and pathological conditions. However, little is known about the involvement of PKM2 in regulating TLR-mediated inflammation and autoimmunity. Herein, we investigated the role of PKM2 in the activation of the TLR pathways and the pathogenesis of inflammation and autoimmune diseases. The activation of TLR4, TLR7 and TLR9 pathways was found to induce the up-regulation of PKM2 expression in macrophages, dendritic cells (DCs) and B cells. The over-expression of PKM2 promotes the activation of TLR4, TLR7 and TLR9 pathways while interference with the PKM2 expression or the addition of the PKM2 inhibitor (PKM-IN) markedly inhibited the activation of TLR4, TLR7 and TLR9 pathways. Mechanistically, PKM2 augmented the activation of TLR4, TLR7 and TLR9 pathways by promoting the activation of the proline-rich tyrosine kinase 2 (Pyk2). Intriguingly, the PKM2 inhibitor PKM2-IN significantly protected the mice from the endotoxic shock mediated by the TLR4-agonist LPS. Additionally, it alleviated the progression in the TLR7-agonist imiquimod-mediated lupus mice and spontaneous lupus MRL/lpr mice. Moreover, PKM2 expression was highly elevated in the monocytes, DCs and B cells from systemic lupus erythematous (SLE) patients compared with those from the healthy donors. Besides, the PKM2 expression level was positively correlated with the degree of activation of these immune cells. In summary, PKM2 contributed to TLR-mediated inflammation and autoimmunity and can be a valuable target to control inflammation and autoimmunity.